Antibacterial Potential of Protein Solution Separated from Bovine Serum by SDS Treatment - Sundaramoorthy, M.; Sabarimanikandan, M.; Aruldoss, G. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
This study explores the separation of antibacterial proteins from bovine serum using a simple and novel method developed. The salt out protein precipitate was prepared from the acid extract of the bovine serum using 30% ammonium sulphate solution. One volume of the precipitate is treated with two volumes of each concentration of SDS solution (1 – 10%) separately in refrigerator temperature. After a week of treatment, two layers are formed. The lower layer is frozen SDS where the upper one is unfrozen protein solution. The upper layer formed by each percentage of SDS was carefully collected and its protein content is also measured. The maximum protein content (90%) has been recovered in the liquid layer formed by 3 % SDS. The λ-max of pooled test protein solution is 276 nm. The Minimum Inhibitory Concentration (MIC) of this protein was checked against seven human pathogenic bacteria and it is ranged from 4 to 1μg. In contrast, there is no heamolysis even at the higher concentration (33 μg) of the test solution. A single mild and faint band with approximate Molecular Weight of 45 kDa is observed in SDS-PAGE. This method of antibacterial protein preparation from cattle serum could lead a new insight in pharmaceutical industries for the development of protein based natural antibiotics.